(3eQBI GdReGfs - (3jhSa Hf pbrRoChrZpdj (B- (3Ch bRZdj (B- (3GHf YHO Gddg, CHh GdeXaQ, TeS GdOjf, SHW CHj GdaQL GHf GdLhRj,J (B654 (3g` s ((3OGQ GdcJH GdeUQjI s)
(3ChdgG (B:s
(3HYO GdHSedI PcQ eGLQj Hjf ChdGO fGUQ GdOhdI CHj GdeXaQ HYK CHh KYdH CNGg GHG JQGH Edi bJGd CNjg GHj GdeXaQ MeOGf UGMH GdhUjI s
(3BNQgG (B:s
(3hceGf CYde GdfGS HQLGd GdMOjK hGdJhGQjN hGdJaGSjQ hcGfJ haGJg aj QHjY GdBNQ HGdCfOdS s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B246 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B324s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3eJaQbGJs